Cost efficiency at South African universities - Serfontein, Carla (University of the Free State, 2022)
Universities are at a crossroads. Globally, the Fourth Industrial Revolution (4IR), expedited by the COVID-19 pandemic, and the looming Fifth Industrial Revolution (5IR) have changed the higher education landscape as we know it. Students can now study at the best universities in the world through technological innovation at a fraction of the cost of traditional university education. Traditional universities have lost their competitive advantage regarding geographic location, relevance, content, and mode of delivery. Universities must adapt to the changing business environment brought about by technological innovation and the 4IR or face the consequences. It seems unavoidable that the enrolments at most traditional universities will decrease significantly in the near future due to increased competition in terms of relevance and more affordable international online education. What happens when students can study more relevant modules for free at the best institutions in the world? What happens to universities if student numbers decline when most university costs are fixed? How will these institutions cover their costs if their funding decreases significantly in an industry notorious for its slow pace of adapting to change? Worldwide it is already happening that student numbers are declining, and universities globally are experiencing major financial sustainability problems (theoretical focus of this study). South African students are poor, with substandard secondary education, seeking relevant, affordable education that will ensure employability. However, all indications are that South African universities failed to meet students’ demands, raising Tuition Fees substantially over the last decade or two and continuing to do so. Declining government subsidies also imply that affordable education is not a given without some drastic changes. The empirical focus of this study was to establish why South African universities had to increase their Tuition Fees over the last decade in times of increasing enrolments and what the potential consequences would be if the student enrolments had to decline in the future. This was the reason why the period of financial analyses was chosen from 2010 to 2019, before the COVID-19 disruption. Traditional universities globally and in South Africa will have to make drastic decisions changing both ‘What’ and ‘How’ they teach. Universities require the thorough application of Management and Cost accounting to obtain relevant and accurate information to aid in their decision-making process to improve their efficiency. However, there exists a gap between the need for universities to apply Management and Cost accounting and the available knowledge on how to use it effectively in the diverse service setting of a university. Therefore, this study's primary objective was to apply Management and Cost accounting principles to assess the efficiency of South African universities as typical service organisations in a disruptive environment. The study used quantitative, exploratory research based on secondary data in the public domain to achieve the primary objective. The Financial Statements from a sample of 16 from the 26 publicly funded universities in South Africa were analysed financially and statistically from 2010 to 2019, using both descriptive and inferential statistics. The sampled universities’ Financial Statements for 2010, 2015 and 2019 were gathered and analysed. The descriptive statistics performed considered the composition and growth of the three Revenue streams and Expense categories of the sampled universities applicable to this study from 2010 to 2019. Inferential statistics were applied using inflation and the growth in Teaching Input and Teaching Output units (TIOUs) to calculate a Budgeted benchmark for the related Revenue streams and Expense categories. These Budgeted benchmarks were then compared to the actual amounts of the related revenue and Expense items and the significance of the difference tested. Regression analysis was also applied to determine the impact of TIOU growth on Total Revenue and Total Expenses as well as the relationship between the Difference in Budgeted and Actual Expenses and Actual and Budgeted Revenue. From the empirical part of this study, it seems that universities did not manage their Expenses efficiently. More concerning is the fact that Expenses increased above inflation and the growth in enrolments. This increase was also primarily a result of increases in Indirect costs; thus an Expense category without any causal relationship to the outputs (number of enrolments) at a university. Universities in South Africa further did not deliver on their objective of providing affordable education that will ensure employability since the increase in Expenses (primarily Indirect) was funded by Tuition Fees rising significantly above inflation and growth in enrolments, justifying the call from students in 2015 that #FeesMustFall.Another critical finding from the empirical part of this study is that universities depended on enrolment growth to fund the increase in Expenses. In an environment dominated by fixed costs, an increase in enrolments should not have resulted in a significant increase in Expenses. Universities should have benefited from Economies of Scale, becoming more efficient in the managing of their Expenses, but this does not seem to be the case. The research questions to be answered are what will happen if enrolments start to decline because of factors such as online teaching becoming the norm, or more affordable and relevant education become available? Add the fact that Salaries represent the major Expense at South African universities in a country with some of the strictest labour laws in the world, how long will it take these universities to become financially viable again? This study provides answers to the stated questions and makes recommendations that could assist universities in applying Management and Cost accounting to manage the disruption they are facing.
Thesis (Ph.D. (Management Accounting))--University of the Free State, 2022
Keywords: Management and Cost accounting; universities; efficiency; Economies of Scale; Direct cost; Indirect cost; decision-making; enrolments; Teaching Input Units; Teaching Output Units; Tuition Fees; Subsidies and Grants; Academic Salaries; Other Salaries